The aesthetic dichotomy beetwen East and West in the novel "My name is red" by Orhan Pamuk - Muñoz Brenes, Tatiana (Tropelías: Review of Literary Theory and Comparative Literature, 2022)
The novel My Name is Red by the Turkish Nobel Prize Orhan Pamuk, reveals the setbacks of the late 16th century Istanbul, in a workshop of miniaturists who face the Western painting’s influence, particularly the so-called Venetian Renaissance. A disjunctive exists between the Islamic pictorial tradition, which seeks the world’s representation through the eyes of God, but without pretensions to usurp his place as the unique and incomparable creator; and its anthropocentric European antithesis, which looks for the exact imitation of reality. This article examines the encounters and disagreements between both cultures and their aesthetic canons present in Pamuk’s text, concluding that more than a conflict with the neighboring culture, it is within itself, in an East-West exchange that remains unequal until our days, where the definition of themselves is sought from the other and from which the History of Art has not been alienated.
Keywords: Pamuk; literature; painting; Islamic art; art history